Antibacterial Alkaloids from Chelidonium Majus Linn (Papaveraceae) Against Clinical Isolates of Methicillin-Resistant Staphylococcus Aureus - Guo Ying Zuo; Fan Yan Meng; Xiao Yan Hao; Yun Ling Zhang; Gen Chun Wang; Gui Li Xu (Frontiers Media S.A., 2009)
Purpose. This study describes the antibacterial effect of extracts and compounds isolated from the aerial part of Chelidonium majus Linn. (Papaveraceae) acting against clinical strains of methicillin-resistant Staphylococcus aureus (MRSA). Methods. The activities were evaluated by using the macrobroth dilution method and reported as the MICs/MBCs. Results. Bioassay-guided fractionation of the most active extract from the aerial parts (EtOAc) led to the isolation of benzo[c]phenanthridine-type alkaloids 8-hydroxydihydrosanguinarine (hhS), 8-hydroxydihydrochelerythrine (hhC), which were potently active against MRSA strains. Conclusions. The selective antibacterial activity reported in this paper for 8-hydroxylated benzo[c]phenanthridine-type alkaloids isolated from C.majus opens the possibility that they could be helpful for the developing of new antibacterial agents for treating the infection of MRSA which has created nosocomial problem worldwide.